Effects of Vitamin E on the Amount of Free Radicals in Traumatized Middle Ear Tissue - (:unkn) unknown (AVES, 2009)
Objective; Tympanosclerosis is a common sequela of tympanoplasty operations causing hearing disability. It is associated with an increased production of free radicals (also known as reactive oxygen species) after trauma. Vitamin E is a scavenger of different free radicals by working as an antioxidant. The aim of the present study was to evaluate the effect of vitamin E-soaked absorbable gelatin sponge placement to the middle ears at quantity of free radicals in rat middle ear. Materials & Methods; This prospective, controlled animal study consisted of Sprague-Dawley rats divided into two groups of 8 animals each. Middle ear trauma was applied following myringotomy to the right ears of the first group and vitamin E-soaked absorbable gelatin sponge were placed to the middle ear of the right ears of the second group. The left ears were used as controls. Then, the animals were killed and chemiluminescence measurements were made for middle ear tissues. Results; Reactive oxygen species levels were significantly increased in right ears of the first group when compared with the control ears (p < .0001), and the levels were significantly decreased in right ears of the second group as compared with the operated ears of the first group (p < .005). The free radical levels of right and left ears in the second group were similar. Conclusion; Our results indicate that vitamin E- soaked absorbable gelatin sponge placement to the middle ear decreases the quantity of reactive oxygen species after trauma.
Keywords: RAT TYMPANIC MEMBRANE; TYMPANOSTOMY TUBE; VENTILATION TUBES; OTITIS-MEDIA; TYMPANOSCLEROSIS; MYRINGOSCLEROSIS; INSERTION; CHILDREN; STAPES